Scenario and sensitivity analysis for flooding vulnerability using genetic algorithms - Apostol, Edward Nataniel C.; Cruz, Joshua Kevin A.; Bongolan, Vena Pearl (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
We minimize flooding vulnerability for a city in the central plain of Luzon by rearranging the barangays (communities or neighborhoods in the city) via a genetic algorithm. The different components of flooding vulnerability were investigated, and each was given a weight, which allows us to express vulnerability as a weighted sum. This serves as the fitness function for the genetic algorithm. We also allowed non-linear interactions among related but independent components, viz, poverty and mortality rate, and literacy and radio/TV penetration. A scenario analysis was done, comparing the city's current state, and the proposed design, and the initial result was a 12 percent decrease in vulnerability with only a one percent increase in cost. Finally, we did a sensitivity analysis on the hazard aspects to improve the fitness function, which effectively changed the initial weights, giving the much improved result of a 24% decrease in vulnerability alongside a 14% decrease in cost units.
Thesis (B.S. Computer Science)--University of the Philippines Diliman
Keywords: Flood damage prevention -- Philippines -- Urdaneta City; Genetic algorithms